2019
DOI: 10.1016/j.jnoncrysol.2019.119643
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Young's modulus of oxide glasses with sparse datasets using machine learning

Abstract: Machine learning (ML) methods are becoming popular tools for the prediction and design of novel materials. In particular, neural network (NN) is a promising ML method, which can be used to identify hidden trends in the data. However, these methods rely on large datasets and often exhibit overfitting when used with sparse dataset. Further, assessing the uncertainty in predictions for a new dataset or an extrapolation of the present dataset is challenging. Herein, using Gaussian process regression (GPR), we pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…Development of reliable composition-property maps for a large class of glass components is the bottleneck impeding the design of new glass compositions. Machine learning (ML) methods [3][4][5][6][7][8] have been used to predict properties such as Young's modulus 9,10 , liquidus temperature 11 , solubility 12 , glass transition temperature 4,13 , dissolution kinetics 5,[14][15][16] , and other properties 17,18 . Most of these works employ traditional glass compositions as descriptors, while some other works employ physics-based descriptors 14,19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of reliable composition-property maps for a large class of glass components is the bottleneck impeding the design of new glass compositions. Machine learning (ML) methods [3][4][5][6][7][8] have been used to predict properties such as Young's modulus 9,10 , liquidus temperature 11 , solubility 12 , glass transition temperature 4,13 , dissolution kinetics 5,[14][15][16] , and other properties 17,18 . Most of these works employ traditional glass compositions as descriptors, while some other works employ physics-based descriptors 14,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…GPR employs a probabilistic approach which makes the inference on new data by learning the underlying distribution (mean and covariance) of the available data 22 . Note that various problems in mechanics and materials science employ a probabilistic framework (including GPR and Bayesian inference) to estimate material parameters 9,[23][24][25][26][27] . It has been shown that for small datasets, GPR models are more suitable in comparison to NN models for providing accurate composition-property predictions along with its confidence intervals in oxide glasses 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, chemical compositions are straightforwardly used as one type of the most common descriptors as they are usually unique for each modeled material, and many material properties are eventually compositional dependent. In fact, several recent works have shown that using chemical compositions only as descriptors can describe the glass properties through the artificial neural network based ML algorithm [20][21][22]52 . However, only using compositional descriptors could make the model have limited extrapolative ability 13,24,26 .…”
Section: Construction Of Descriptorsmentioning
confidence: 99%
“…In this section, predictions based on GP regression (see "Methods" section) are the focus. Two kernels i.e., radial basis function (RBF) and Matern kernels which are commonly adopted in the literature and also have been shown to produce accurate results 38 are implemented here. Figure 5 shows the predicted elastic constants using GPR with rbf kernel against the measured values computed by MD simulation.…”
Section: Prediction Of Elastic Constants Using Gaussian Process (Gp)mentioning
confidence: 99%